Affective forecasting and self‐control: Why anticipating pride wins over anticipating shame in a self‐regulation context - Patrick, Vanessa M.; Chun, HaeEun Helen; Macinnis, Deborah J. (Journal of Consumer Psychology, 2009)
AbstractWe demonstrate that anticipating pride from resisting temptation facilitates self‐control due to an enhanced focus on the self while anticipating shame from giving in to temptation results in self‐control failure due to a focus on the tempting stimulus. In two studies we demonstrate the effects of anticipating pride (vs. shame) on self‐control thoughts and behavior over time (Studies 1 and 2) and illustrate the process mechanism of self vs. stimulus focus underlying the differential influence of these emotions on self‐control (Study 2). We present thought protocols, behavioral data (quantity consumed) and observational data (number/size of bites) to support our hypotheses.